Optimizing resources in genomic surveillance: South Carolina’s QC-plus approach - Cox, Rachel; Goodwin, Gregory; Freeman, Jessica; Godfrey, Gabrielle; Kapingidza, Anyway; Smith, Andrew; Scott, Julia; Diedhiou, Abdoulaye; Buru, Karla; Weaver, Cory J.; Adair, Ona; Meredith, Jenny; et al. (Frontiers in Public Health, 2025)
Whole genome sequencing (WGS) is the gold standard for identifying emerging variants during epidemics but is resource intensive. Traditionally, a low RT-qPCR cycle threshold (Ct) is used to select samples with presumed high viral loads but whether better alternatives exist is unclear. This study introduces and evaluates a Ct-independent method, SCQC-Plus (SCQC+) approach, combining enhanced library preparation and agarose gel-based quality control for selecting samples for sequencing. From June 2022 through December 2024 at the state public health laboratory, over 1,800 SARS-CoV-2 positive clinical samples were sequenced and studied in two phases: retrospectively and prospectively. In the first phase when all PCR positive samples received into the laboratory were sequenced, we simulated the impact of two Ct-restriction thresholds (Ct < 28 and Ct < 30) by excluding those samples from the data. In the prospective phase, we tested three selection strategies on sequencing efficiency: Seq-All, Ct < 30, and SCQC+. Lastly, we compared the variants captured by a centralized state public health laboratory with those of commercial and clinical labs in the state. Results from the retrospective study suggested that Ct restriction of 30 was cost effective but missed variants in circulation. Prospectively, we found that the SCQC+ approach had a comparable cost effectiveness to Ct-restricted approach. Notably the SCQC+ approach halved the fail rate for samples with Ct over 30, resulting in the sequencing of two variants not found among samples with Ct under 30. Finally comparing the variants detected by commercial and clinical laboratories in the state identified unique variants not detected in the sampling of the state public health laboratory. This observation suggested the importance to public health of maintaining such partnerships to enable timely and comprehensive variant surveillance program. The goal of the sequencing program can impact the cost effectiveness of different approaches for sample selection. When the goal is the early detection of emerging or rare variants of concern prior to wide dispersal into the population, we propose a combination of the SCQC+ approach internally and partnership with in-state commercial and clinical laboratories, externally, as important requirements for achieving that goal.